Contribution of the results‐based financing strategy to improving maternal and child health indicators in Burkina Faso. (16th August 2018) - Zizien, Zawora Rita; Korachais, Catherine; Compaoré, Philippe; Ridde, Valéry; De Brouwere, Vincent
Summary: In response to the poor performance of its public health care provision, Burkina Faso decided, to implement results‐based financing (RBF). This strategy relies on a strategic purchase of the quantity and quality of services provided by health workers, monitored by a set of indicators. However, there is a lack of evidence on its effects. The objective of this article is to appreciate the effect of RBF on a set of maternal and child health (MCH) indicators in Burkina Faso. The study design is quasi‐experimental comparative with a control group before and after the implementation of the RBF. To estimate the effect of RBF, we used two methods of analysis: (1) the segmented regression to measure the effect of RBF in the health districts (HD) implementing RBF (RBF HD) and (2) the difference‐in‐difference test to estimate the effect of RBF considering the differences in mean between RBF HD and HD that did not implement RBF (non–RBF HD). We found among five indicators studied that only the postnatal consultation coverage in RBF HD was significantly higher (7.68%; P = 0.04) than in the non–RBF HD. Overall, our findings do not clearly demonstrate the effectiveness of RBF in improving MCH indicators in Burkina Faso.